2014
DOI: 10.5901/mjss.2014.v5n15p575
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Work-Related Stress among High School Teachers in the Hhohho Region of Swaziland

Abstract: This study sought to investigate the work-related stress among high school teachers in the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 47 publications
0
5
0
1
Order By: Relevance
“…A study by Dlamini, Okeke and Mammen from 2014 has indicated that badly planned changes were a major source of work - related stress among teachers in Swaziland [ 14 ]. Changes in education as a major factor among sources of work - related stress among teachers were also reported by studies conducted in South Africa and Zimbabwe in 2002 [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study by Dlamini, Okeke and Mammen from 2014 has indicated that badly planned changes were a major source of work - related stress among teachers in Swaziland [ 14 ]. Changes in education as a major factor among sources of work - related stress among teachers were also reported by studies conducted in South Africa and Zimbabwe in 2002 [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies (Okeke & Dlamini, 2013;Dlamini et al, 2014;Afshar & Doosti, 2016), pointed out that positive work environment was very important for the workersí physical, mental and emotional health. According to Khan (2003), favourable working conditions would boost teachersí job satisfaction.…”
Section: Views On Causes Of Dissatisfactionmentioning
confidence: 99%
“…Research findings indicated that a majority of the respondents were intrinsically motivated; 90 percent of these teachers agreed that they chose the teaching profession because they had passion for teaching. Skaalvik and Skaalvik (2007), Okeke and Dlamini (2013), Dlamini et al (2014), Afshar and Doosti (2016) found that teachersí self-efficacy influenced their teaching behaviour and their studentsí motivation and achievement. Self-efficacy is a personís judgment about being able to perform a particular activity.…”
Section: Aspirations To Become a Teachermentioning
confidence: 99%
“…Amidst these activities, stress may be inevitable. Consequently, teachers' stress has been a subject of research for many decades (Dlamini and Okeke et al, 2014;Pandey, 2015). Traditionally, teaching profession was believed to be a low stress occupation (French, et al 1982as cited in Parray, et al 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, teaching profession was believed to be a low stress occupation (French, et al 1982as cited in Parray, et al 2016. However, in the past decades, researchers have shown that all over the world, teaching profession is a stressful occupation (Manabete et al, 2016, Precey, 2015, Dlamini and Okeke, et al, 2014, Nwosu and Ayodele, 2011Alan et al, 2010), at all levels from the elementary to university level (Parray, et al, 2016). As such, researchers have gradually become more interested in examining stress in the teaching profession.…”
Section: Introductionmentioning
confidence: 99%